2020
DOI: 10.2147/cmar.s267357
|View full text |Cite
|
Sign up to set email alerts
|

H19 Rises in Gastric Cancer and Exerts a Tumor-Promoting Function via miR-138/E2F2 Axis

Abstract: Purpose The aim of this paper was to investigate H19 expression in gastric cancer (GC) and its effects on the biological behavior of gastric cancer cells (GCCs), and at exploring its potential mechanism. Methods H19 expression in the patients’ tissues and serum was detected, and the correlation of the expression with the patients’ pathological data and survival rate was analyzed. Overexpression or inhibitory vectors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…We assessed the quality of included studies using NOS and found that the quality of the enrolled studies was acceptable. Thirty-eight studies [ 9 , 12 , 14 , 21 27 , 29 31 , 33 , 34 , 36 , 38 40 , 42 , 46 50 , 52 55 , 57 , 62 , 63 , 65 , 66 ] were of high quality while the other 16 studies [ 28 , 32 , 35 , 37 , 41 , 43 , 47 , 51 , 56 , 58 61 , 64 , 67 ] were of moderate quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the quality of included studies using NOS and found that the quality of the enrolled studies was acceptable. Thirty-eight studies [ 9 , 12 , 14 , 21 27 , 29 31 , 33 , 34 , 36 , 38 40 , 42 , 46 50 , 52 55 , 57 , 62 , 63 , 65 , 66 ] were of high quality while the other 16 studies [ 28 , 32 , 35 , 37 , 41 , 43 , 47 , 51 , 56 , 58 61 , 64 , 67 ] were of moderate quality.…”
Section: Resultsmentioning
confidence: 99%
“…Sample types included tissue [9,11,, circulating (plasma and serum) [12,13,47,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], and gastric juice [21,64,66]. Most studies took specimens from Chinese population, and six studies took samples from Japanese [49],…”
Section: Literature Search and Studymentioning
confidence: 99%
“…It is reported that H19 plays a critical role in all stages of tumorigenesis, highlighting the carcinogenic effects of H19 in a variety of cancers, such as gastric, hepatocellular, and pancreatic carcinoma. [18][19][20] Most studies have indicated that H19 is associated with growth, migration, invasion, and/or metastasis in many cancers, and serum H19 levels in patients with certain cancers have been suggested to be useful for diagnosis and prognosis. 21 Similarly, we found that H19 expression was upregulated in OC tissues and cells, and H19 overexpression was associated with poor prognosis of OC patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…E2F2 expression was reported to be upregulated in gastric cancer (26,27), which is in accordance with the data of the present study. Additionally, H19 was demonstrated to promote gastric cancer cells to proliferate and invade through the miR-138/E2F2 axis (28). In cisplatin-resistant gastric cancer cells, miR-26a could improve the sensitivity of GC cells to cisplatin-based chemotherapies through E2F2 (29).…”
Section: Discussionmentioning
confidence: 99%